Formulating of scientific problem in the theory of combat service support in the Interior Troops - Rolin І. F. (Honor and Law, 2019)
The result of studies of the theory of combat service support in the Interior Troops and their activities are given, the contradiction between initial empirical and theoretical grounds of the above mentioned theory as for the Interior Troops is grounded; the scientific problem is formulated.